Current concepts in treatment of early knee osteoarthritis and osteochondral lesions; the role of biological augmentations - Dall'Oca, C.; Cengarle, M; Costanzo, A.; Giannini, N; Vacchiano, A; Magnan, B. (Acta Biomedica Atenei Parmensis, 2017)
Early knee osteoarthritis and chondral lesions are a common cause of disability in younger patients. Surgical options, such as microfractures, ACI and OAT, provide good, but not fully satisfying, outcomes. Recent advance in biological knowledge introduced two different methodological approaches of delivering growth factors and stem cells into the articular environment. Platelet-Rich Plasma and Mesenchimal Stem Cells are supposed to change the way to approach early knee osteoarthritis and chondral lesions, though their indications and limits are yet to be determined.